2020
DOI: 10.3390/v12020166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TDP2/VPg Unlinkase Activity on Picornavirus Infections Downstream of Virus Translation

Abstract: In this study, we characterized the role of host cell protein tyrosyl-DNA phosphodiesterase 2 (TDP2) activity, also known as VPg unlinkase, in picornavirus infections in a human cell model of infection. TDP2/VPg unlinkase is used by picornaviruses to remove the small polypeptide, VPg (Virus Protein genome-linked, the primer for viral RNA synthesis), from virus genomic RNA. We utilized a CRISPR/Cas-9-generated TDP2 knock out (KO) human retinal pigment epithelial-1 (hRPE-1) cell line, in addition to the wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Over the years, several other host nuclear proteins have been identified that interact with specific structural elements of the RNAs of enteroviruses and other picornaviruses, however, the full extent of the effects exerted by the complex mixture of the nuclear RNA-binding factors that are translocated to the cytoplasm upon infection is still poorly understood [ 15 , 27 ]. Interestingly, the accumulating evidence demonstrates that none of these RNA binding and/or processing proteins is absolutely required for enterovirus infection, suggesting a significant redundancy of the host protein functions in supporting viral RNA translation/replication cycle [ 22 , 23 , 28 , 29 ]. Rather, the cumulative effect of multiple host proteins on viral RNA stability, translation, and replication efficiency is likely cell type-dependent, and may contribute to the determination of viral tropism in the host [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several other host nuclear proteins have been identified that interact with specific structural elements of the RNAs of enteroviruses and other picornaviruses, however, the full extent of the effects exerted by the complex mixture of the nuclear RNA-binding factors that are translocated to the cytoplasm upon infection is still poorly understood [ 15 , 27 ]. Interestingly, the accumulating evidence demonstrates that none of these RNA binding and/or processing proteins is absolutely required for enterovirus infection, suggesting a significant redundancy of the host protein functions in supporting viral RNA translation/replication cycle [ 22 , 23 , 28 , 29 ]. Rather, the cumulative effect of multiple host proteins on viral RNA stability, translation, and replication efficiency is likely cell type-dependent, and may contribute to the determination of viral tropism in the host [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…1j) [34][35][36] . These activities are critical for cell fitness, as their inhibition results in p53 activation, and cell cycle arrest even in the absence of exogenous DNA damage 28,29,31,37 , as seen upon loss of TRIM52 8 . Therefore, we hypothesized that TRIM52 plays a role in the repair of TOP2-associated DSBs, playing an important function in the TDP2-dependent HDR pathway (Fig.…”
Section: Trim52 Is Required For Resolution Of Top2-mediated Dna Lesionsmentioning
confidence: 99%
“…Picornaviruses have been shown to hijack a host protein, TDP2, to cleave the phosphodiester bond linking VPg to the genomic RNA, with this RNA becoming the template for translation [ 48 , 49 , 50 ]. In addition to a polymerase, viruses in the picornavirus family require cis-acting RNA elements for VPg nucleotidylylation and replication of the viral genome.…”
Section: Picornavirusesmentioning
confidence: 99%